(untitled) (FULafia Journal of Science and Technology, 2026)
This physics-based study quantitatively investigates the contravention of the atmospheric environmental lapse rate within multi-storey buildings in a tropical savanna climate (Lafia, Nigeria; 8.480°N, 8.520°E), where indoor thermal gradients invert due to solar gain and stack effect. The aim was to measure the magnitude of vertical temperature stratification across seasons in two three-storey buildings (academic, residential). Using a calibrated infrared thermometer (±1.0 °C), temperatures were measured at three heights per floor (0.3, 1.2, 2.1 m) at 09:00, 14:00, and 18:00 h over the dry (February), early rainy (June), and late rainy (September) seasons. Results show a consistent positive gradient, peaking at 1.1 °C (Social Science) and 0.9 °C (Hostel) in the dry season, with upper-floor temperatures reaching 38.8 °C. The mean vertical gradient attenuated seasonally from 0.70 °C (February) to 0.40 °C (June) and 0.25 °C (September), a 64 % reduction, while the academic building exhibited a steeper annual gradient (0.45 °C) than the hostel (0.39 °C). The findings demonstrate that buoyancy-driven heat accumulation imposes a quantifiable thermal penalty on upper floors. Consequently, we recommend integrating specific passive physics controls: high-albedo (>0.7) reflective roofing, enhanced roof insulation (R-value > 3.5 m²K/W), and optimized cross-ventilation (target ACH > 15–20) to disrupt stratification and reduce dry-season cooling loads.